Development and Testing of a Graphical FORTRAN Learning Tool for Novice Programmers - Ajayi, A. O.; Soriyan, H.A.; Akinboro, S. A.; Olajubu, E. A.; Ninan, D. F. (Interdisciplinary Journal of Information, Knowledge, and Management, 2023)
Interdisciplinary Journal of Information, Knowledge, and Management, volume 5, p.278-290.